ANALYZE FACTORS THAT AFFECT ENTREPRENEURS OF MICRO, SMALL, MEDIUM ENTERPRISES INTENTION TO USE ACCOUNTING INFORMATION SYSTEMS BASED ON FLOW THEORY - Debbianita Debbianita; I Nyoman Agus Wijaya; Ita Salsalina Lingga; Maria Maria (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
This study aims to analyze factors that affect entrepreneurs of micro, small and medium enterprises (MSME) intention to use accounting information systems (AIS). This research model is based on theory of flow which analyzes attitude towards AIS Use, Perceived Enjoyment and Concentration as factors that affect behavioral intention to use and its impact to actual usage. Analysis of data uses Partial Least Square (PLS) of Structural Equation Modeling (SEM). Unit of analysis in this research are entrepreneurs of Micro, Small, and Medium Enterprises (MSME) in Bandung City. In order to obtain primary data, we use questionnaires. The result of this research is intended to solve the problem of low intention to use AIS which gives impact to AIS usage.